Prioritization of watersheds for soil and water conservation based on GIS, PCA and WSA techniques - López-Silva, Maiquel; Carmenates-Hernández, Dayma (Tecnología y ciencias del agua, 2023)
Soil and water conservation is a priority in the watersheds of arid and semi-arid regions for the proper planning and integrated management of water resources. The objective of this work is prioritizing 91 watersheds in 14 regions of Peru with different geographical, hydrological and geological conditions, through the integration of Geographic Information Systems (GIS), Principal Component Analysis (PCA) and the Weighted Sum Approach (WSA). In addition, homogeneous regions were identified with hierarchical Cluster Analysis in R and Ward’s method. The result showed the existence of 19.49 % of total area in high and very high priority category in two regions. The results of the Cluster Analysis showed that 35 % of the watersheds have homogeneous zones within the geometric and shape factor, while 65 % within the drainage and relief factor. In general, GIS, PCA and SWA methods are an efficient tool, which allows decision-making authorities for better planning and conservation of natural resources in hydrographic watersheds.